The wow and the how : the role of arts education and approaches for teaching - Bamford, Anne (2021)
Society is facing considerable disruptions. To name but a few we have seismic changes in technology, in the nature of work,in the environment, in inequality, in patterns of life and migration, in health and wellbeing, and in the mistrust of institutions. Above all, we have become increasingly at the mercy of very rapid changes. The arts, and specifically arts education, help to prepare us to learn and to flourish in the world now and in the future. Párrafo extraído del artículo a modo de resumen